Evaluation of polyphenolic profile and nutritional value of non-traditional fruit species in the Czech Republic--a comparative study - Jurikova, Tunde; Sochor, Jiri; Rop, Otakar; Mlček, Jiří; Balla, Stefan; Szekeres, Ladislav; Zitný, Rastislav; Zitka, Ondrej; Adam, Vojtech; Kizek, Rene (Molecules, 2012)
Dry matter, organic acids, ascorbic acid, minerals (nitrogen, phosphorus, potassium, calcium, magnesium, sodium) and polyphenolic profile of a number of non-traditional fruit species and their genotypes, namely blue honeysuckle (Lonicera spp.), Saskatoon berry (Amelanchier alnifolia), black mulberry (Morus nigra), Tomentosa cherry (Prunus tomentosa Thunb.) and jostaberry (Ribes nigrum x Grossularia uva-crispa) were investigated. The results showed that Lonicera genotypes displayed high levels of ascorbic acid and they were rich in minerals, with the cultivar ‘Amfora’ achieving the leading position in nitrogen, phosphorus and potassium content among all lesser known fruit species. Amelanchier cultivars represented a valuable source of ascorbic acid and calcium, ‘Tišňovský’ and ‘Smoky’ together with Morus nigra ‘Jugoslavska’ accumulated the highest level of examined polyphenolic compounds. Regular consumption of studied less common fruit species can bring health benefits so they can represent a high potential value for fruit growers and in addition they can be utilised as functional foods.
Keywords: nutriční hodnota; Morus; kyseliny nekarboxylové; Česká republika; Prunus; Carboxylic Acids; Genotype; Rosaceae; genotyp; minerály; Ribes; Czech Republic; Nutritive Value; ovoce; Polyphenols; slivoň; Lonicera; kyseliny karboxylové; Fruit; rostlinné extrakty; Plant Extracts; Minerals; polyfenoly; Acids, Noncarboxylic